2015
DOI: 10.15446/rsap.v17n3.44076
|View full text |Cite
|
Sign up to set email alerts
|

Desafios para a inserção do fisioterapeuta na atenção básica: o olhar dos gestores

Abstract: Objective Study aimed to identify how physical therapists are included in primary care (PC), the perspectives of health managers, and the role that the inclusion of this professional in the health team plays. Methods Qualitative study involving health secretaries of 22 municipalities in southern Brazil. Results 45 physiotherapists in the region were included in PC. One of these was in the Family Health Strategy (FHS), and two were in the Nuclei of Support to Family Health (NSFH). 13 administrators cited the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 9 publications
0
3
0
16
Order By: Relevance
“…By reading the selected studies, it was identified that the majority of the research on the subject is related to the performance of a particular professional category belonging to the NASF-AB. [17][18][19][20]22 Only one study dealt specifically with the actions carried out in the basic carefrom the NHPEP aimed at the elderly population, however portraying the professionals in general and of these the NASF-AB and only two studies brought the actions of the NASF-AB multiprofessional team, one from which the users perceived the proposal and one in relation to the service profile aimed at rehabilitation. 16,21,23 It was observed the predominance of studies that address health promotion practices through bodily practices and physical activities, as described in Table 2 that brings the health promotion practices performed by NASF-AB professionals.…”
Section: Resultsmentioning
confidence: 99%
“…By reading the selected studies, it was identified that the majority of the research on the subject is related to the performance of a particular professional category belonging to the NASF-AB. [17][18][19][20]22 Only one study dealt specifically with the actions carried out in the basic carefrom the NHPEP aimed at the elderly population, however portraying the professionals in general and of these the NASF-AB and only two studies brought the actions of the NASF-AB multiprofessional team, one from which the users perceived the proposal and one in relation to the service profile aimed at rehabilitation. 16,21,23 It was observed the predominance of studies that address health promotion practices through bodily practices and physical activities, as described in Table 2 that brings the health promotion practices performed by NASF-AB professionals.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 In the context of the primary healthcare facilities, these professionals can be involved in searching for vulnerable groups for chronic diseases, promoting actions and campaigns to stimulate healthy lifestyles, offering support and guidance to caregivers in the falls prevention, and in construction of areas for the practice of physical activity practices, among other activities. 25,26 The potential barriers to inclusion of physiotherapists in the public primary healthcare include the lack of prioritization in the allocation of budget funds 27 and a limited knowledge toward physiotherapy field among the users of the services. 28 Despite these problems and considering the elderly population, it is known that the advances in primary care can influence the reduction of hospitalizations due to sensitive conditions to primary care, 29,30 and the physiotherapy plays a key role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Observou-se que nos municípios onde existe atuação do Incidência dos encaminhamentos de fisioterapia das UBS de Gurupi -TO A fisioterapeuta como importante profissional na composição da equipe de saúde da ESF ou NASF, uma contribuição significativa para a qualificação das ações de saúde junto à comunidade e a resolutividade de um sistema de saúde universal, integral e equitativo. 13 Ademais o NASF-AB é essencial na manutenção da saúde visto que as demandas necessitam de diversas especialidades para aumentar a resolutividade e abrangência dos serviços ofertados pela AB propondo visitas para acompanhamento do usuário, orientação aos cuidadores e às ACS no processo de reabilitação, visando a atenção com responsabilidade dos envolvidos no cuidado e não somente na dependência do usuário à presença do fisioterapeuta. O fisioterapeuta, segundo as diretrizes da ESF desenvolve ações promovendo serviços para tratamento e reabilitação, além da atuação na prevenção de agravos e doenças da população tanto de modo individual como em ações coletivas, por isso que é muito importante que aja uma boa estrutura física, materiais e capacitação dos profissionais isso influencia o andamento dos atendimentos favorecendo a um bom desfecho e levando a resolutividade das necessidades dos usuários do SUS.…”
Section: Materiais E Métodosunclassified